Integration of Local Wisdom and Modern Governance in Preventing and Handling Violence at Pesantren Terpadu Al Mujaddid - Chairil, Chairil; Salami, Salami; Saiful, Saiful (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This study investigates how Pesantren Terpadu Al Mujaddid, Sabang, integrates Acehnese local wisdom with modern governance to prevent and handle violence within the boarding school environment. Although previous studies have addressed violence in pesantren, limited attention has been given to models that combine traditional Acehnese conflict-resolution mechanisms with technology-based supervision in a unified framework. Using a qualitative case study design, data were collected through interviews, observations, documentation, and autoethnography involving pesantren leaders, caregivers, teachers, students, and parents. The findings reveal four key preventive strategies: technology-assisted supervision through CCTV and digital reporting, transparent communication with parents, digitalized financial management to reduce theft-related conflicts, and routine deliberation for early detection of behavioral issues. In terms of case handling, the pesantren employs Acehnese customary practices-duek pakat (communal deliberation), suloh (customary mediation), and diyat (compensation)-as restorative mechanisms that involve both families, community elders, and pesantren authorities. Parents express strong trust in this integrative system due to its transparency, cultural relevance, and emphasis on child protection. This study contributes a contextualized governance model for Islamic boarding schools that harmonizes local cultural wisdom and modern administrative tools to create a safe, educative, and culturally grounded pesantren ecosystem.